(untitled) (Nigerian Journal of Physiological Sciences, 2022)
This study was designed to investigate the phytochemical composition and protective effects of methanol extract of Parquetina nigrescens leaf (MEPL) in male Wistar rats. Phytochemical screening, in vitro antioxidant assay, gas chromatography-mass spectrometry (GC-MS) and LD50 were determined. Forty male Wistar rats were grouped into eight and orally treated for 54 days as follows: Group 1 (10% tween 80), Group 2 (3 mg/kg As2O3) Groups 3, 4 and 5 (250, 500 and 1000 mg/kg MEPL) and groups 6, 7 and 8, (250 mg/kg+As2O3, 500 mg/kg+As2O3 and 1000 mg/kg+As2O3). The animals were sacrificed on day 55 under anaesthesia. Blood was collected by cardiac puncture for heamatological studies. Liver concentrations of malondialdehyde (MDA), superoxide dismutase (SOD), aspartate aminotransferase (AST), alanine amino transferase (ALT) and alkaline phosphatase (ALP) activities were determined spectrophotometrically. Liver histology was also assessed. Flavonoids, tannin, alkaloids, saponin, and anthraquinone were present in MEPL, also, MEPL scavenged 2,2 diphenyl-1-picrylhydrazyl hydrate (DPPH) and Azino-bis-3-ethylbenzthiazoline-6-sulphonic acid radical (ABTS+). The IC50 of MEPL required to chelate metal was also low. The GC-MS revealed the presence of 24 essential oil. The LD50 was > 5000 mg/kg. Packed cell volume and red blood cell count were significantly reduced in 1000 mg/kg MEPL group, white blood cell count and SOD activity reduced (P<0.05) in 3 mg/kg As2O3 when compared with control but increased in groups co-treated with As2O3 and 250, 500 or 1000 mg/kg + As2O3. MDA concentration, AST, ALT and ALP activities increased significantly in 3 mg/kg As2O3 group but decreased (P<0.05) in groups co-treated with As2O3 and 250, 500 or 1000 mg/kg. The methanol extract of Parquetina nigrescens leaf in male Wistar rats has antioxidant, hepatoprotective and white blood cell protective effects.